MiRNAs levels in a Streptozocin model of Alzheimer’s disease - Moustafa, Nada (AUC Knowledge Fountain, 2022)
Dementia entails a progressive decrease in cognitive functions, with 50%-75% of cases attributed to Alzheimer’s disease (AD); an aging-associated condition characterized by the build-up of tangled phosphorylated Tau (p-Tau) protein and beta-amyloid (Aβ) depositions. Sporadic AD (sAD) is multifactorial in nature, resulting from a combination of environmental and genetic predisposing factors. Type 2 diabetes mellitus (T2DM) is a leading risk factor for dementia, and deregulation of brain glucose metabolism is associated with early cognitive affection in sAD. Thus, the diabetogenic agent Streptozotocin (STZ) is used to experimentally create an AD model in animals (STZ-induced sAD), in which abnormalities in cerebral glucose metabolism and insulin signaling take place. Furthermore, microRNAs are investigated for their potential role in AD. Among these, Let-7s were shown to exert neurotoxic effects and share in the regulation of glucose metabolism and peripheral insulin resistance. MiR-107 endogenously suppresses Let-7s, and it was found to be downregulated in the brains of AD patients. There are also reports of its dysregulation in diabetes. However, miR-107 brain expression in the STZ-induced sAD model is yet to be studied. Thus, we aimed to investigate the brain levels of selected Let-7s and miR-107 in the acute and chronic phases of STZ-induced sAD in rats. 54 Adult Sprague Dawley rats were subdivided into 6 equal groups: young intact, young CSF (vehicle control), acute STZ, old intact, old CSF, and chronic STZ. In the STZ groups, sAD was induced by stereotaxic injection of STZ in the lateral ventricles. Acute STZ group and age-matched controls were tested 3 weeks after STZ injection, while chronic STZ group and age-matched controls were tested 3 months after the injection. Open-field tests and T-maze were used for behavioral and cognitive assessments, respectively. Hippocampi were extracted and examined for p-Tau (Ser396) concentration, Let-7a, b & e and miR-107 expression profiles as well as histopathological changes. Results showed reductions in cognition and locomotor activities along with increased anxiety-related behaviors in the STZ-model groups. P-Tau was elevated in the model groups and old controls, with the chronic STZ group having the highest mean concentration. Let-7 miRNAs did not exhibit any change in expression in any group, while miR-107 was upregulated in the STZ-model groups. Histopathological examination revealed AD-like neurodegenerative changes in the hippocampi of STZ-model rats. These results further confirm the criteria of the STZ AD model and add to the evidence of potential involvement of miR-107 in AD processes.